Bioarchaeological analysis of Castelsardo’s Mummies - Mazzarello, Vittorio; Chessa, Daniela; Delaconi, Paola; Marongiu, Patrizia; Kelvin, David J.; Kelvin, Nikky; Campus, Franco; Demurtas, Maria Antonietta; Sanna, Luca; Pomponi, Valeria; et al. (Italian Journal of Anatomy and Embryology, 2015)
In the early months of 2011, during the restoration of Sant’Antonio Abate’s Cathedral in Castelsardo came to light environments remained hidden so far, which aroused considerable interest both for the archaeological and anthropological point of view for the discovery of a cemetery crypt with numerous human remains dating from the eighteenth to nineteenth century. Archaeological investigations took place at different times and in different ways during the months of January to April of 2011, which allowed to detect a burial site, with a great number of individuals organized in several layers piled up at the bottom of the crypt, and to define some stages in the building of the church, mainly in its monumental transition from Romanesque structure to new cathedral seat of the diocese. Eighteen individuals of both sexes, were finally identified at different levels, including 16 partially mummified and 2 almost entirelly mummified deposited on a sort of open plank, that, from the archeological point of view, represented the crypt closing point. The found remains were studied in order to obtain interesting bioarchaeological information determining some peculiar characteristics regarding the medical and the scientific aspects, more precisely age of death, sex, stature in life, pathological conditions, and to evaluate the state of conservation of mummified tissues, describing the morphological characteristics by histological, immunohistochemical and ultrastructural techniques.